Association of adult attention deficit hyperactivity disorder subtypes and response to methylphenidate HCL treatment: A magnetic resonance spectroscopy study. (14th September 2015) - Unal, Gonca Ayse; Kenar, Ayse Nur Inci; Herken, Hasan; Kiroglu, Yilmaz
Highlights: The effects of MPH on NAA, Cho, and Cr are examined in different subtypes of ADHD. No significant change was determined in brain metabolite levels after MPH between the subtypes. Choline levels increased after MPH in striatum in combined type. Abstract: The effects of methylphenidate (MPH) treatment on N -acetyl aspartate (NAA), choline and creatine are being examined in individuals with different subtypes of attention deficit hyperactivity disorder (ADHD). Sixty ADHD subjects were included into the study aging between 18 and 60 years. Levels of NAA, creatine and choline in anterior cingulate cortex, cerebellum, striatum and dorsolateral prefrontal cortex were measured with magnetic resonance spectroscopy. Then, 10 mg oral MPH was given to the subjects and the same metabolite levels were measured after an interval of 30 min. Distribution of the patients according to the ADHD subtypes was as follows: 21 of them (35.0%) were in the inattentive type, 11 of them (18.3%) were in the hyperactive type and 28 of them were (46.7%) in the combined type. Changes of brain metabolite levels after MPH were found not to be statistically significantly different between the subtypes. The increase of choline levels after MPH compared to the levels of choline before MPH in striatum in the combined type patients were statistically significant. No clear association was found between ADHD subtypes and changes of brain metabolites with use of MPH in adult ADHD.